ANALISIS PERHITUNGAN DAN PELAPORAN PPh PASAL 22 ATAS PENJUALAN BARANG PADA CV BERKAT NAULI - Djefry Tulangow; Ventje Ilat; Stanley Kho Walandouw (Universitas Sam Ratulangi, 2023)
In Indonesia, taxes are one of the obligations that must be paid by every citizen. As a company that has Article 22 PPh obligations, the company has attempted to organize bookkeeping, deposit and reporting of Article 22 PPh to fulfill Article 22 PPh obligations. The PPh Article 22 accounting process has its own specifications that must be understood by every taxpayer. The goal to be achieved in this study is to find out the application of calculating, recording, depositing, and reporting income tax article 22 on the sale of goods at CV Berkat Nauli. The type of research used in this study is a type of qualitative research with a descriptive approach. This research was conducted directly to the data source by collecting, presenting, and analyzing data obtained from observations or existing documents. Article 22 PPh on CV Berkat Nauli from the process of calculating and collecting the proceeds from the sale of goods not yet based on Minister of Finance Regulation number 107/PMK.010/2015.